Solvability of a boundary value problem with a Nagumo Condition. Issue 4 (4th July 2018) - Khaldi, R.; Guezane-Lakoud, A.
ABSTRACT: The aim of this paper is to discuss the existence and localization of solutions for a generalized Emden-Fowler equation involving a conformable derivative and with a Dirichlet boundary condition. Our approach is based on the lower and upper solutions method and Schauder fixed-point theorem under a Nagumo condition.